Architectural diversity and galling insects on Caryocar brasiliense trees - Demolin Leite, Germano Leao; Veloso, Ronnie Von dos Santos; Zanuncio, Jose Cola; Azevedo, Alcinei Mistico; Silva, Julia Leticia; Wilcken, Carlos Frederico [UNESP]; Soares, Marcus Alvarenga (Nature Publishing Group, 2017)
Galling insects are a highly sophisticated herbivore group on Caryocar brasiliense, a tree that represents the main income source for many communities. The effect of architectural diversity of C. brasiliense trees on galling insect community diversity and abundance was studied. The abundance of adult insects and galled leaves were seven and 1.6 times higher in trees with a greater height/width of canopy (RHW) ratio, respectively. Gall parasitoid richness was 1.8 times greater on trees with higher RHW. Zelus armillatus (Lepeletier & Serville) (Hemiptera: Reduviidae) and ant numbers were 5.8 and 2.7 higher on trees with the largest and smallest RHW, respectively. More complex plant architectures favored species diversity for galling insects and their natural enemies. The competition among four galling insect species for space and feeding and the evidence of prudence strategy were, for the first time, observed for galling insects in the Brazilian Cerrado biome.